Mobile Ontology Design for Semantic Web: A Case Study - Banu, W. Aisha; Abdul Khader, P.Sheik; Shriram, R. (Malaysian Journal of Computer Science, 2011)
The era of ubiquitous computing and communication has started to change the dynamics of design of systems in a big way. Mobile computing has become the norm and solutions that can automatically understand user intent are the need of the hour. For this, ontology design for mobile computing is crucial. Designing ontology systems that are tailored towards heterogeneous mobile environments imposes demands such as data management, reasoning systems and memory efficiency. The systems must be expressive to include the dimensions of the context, scalable and focused towards the users. In this paper we discuss the design of the ontology for mobile environment and a semantic encoding system that can manage the data. The experimental results show the promise of the work and applicability to various operations in the domain.